2019
DOI: 10.1108/qae-04-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

Business simulation and assurance of learning

Abstract: Purpose This study aims to consider assurance of learning among undergraduate business students enrolled in capstone business strategy courses using the GLO-BUS competitive simulation. Gender, academic major and business core course performance were examined. Design/methodology/approach Participants were 595 undergraduate capstone business students from 21 course sections taught over a four-year period. Variables included learning assurance measures, simulation performance, gender, major, business core cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Learning is a cognitive process, where learners process new knowledge based on prior knowledge (Ghadirian et al, 2018); New knowledge is best captured by learners when it is rooted in a context or environment familiar to the learner (Podschuweit and Bernholt, 2018); Experiential learning stimulates knowledge acquisition and processing (Sung et al, 2017;Alstete and Beutell, 2019;Bassi, 2019); New knowledge is first processed by the sensory memory, then by short-term memory, and finally is stored in long-term memory (Nissen and Stenliden, 2020); and Learning is a social activity; learning in small groups is associated with the better achievement of interpersonal skills and positive attitudes toward the learning environment and thinking skills (Wyness and Dalton, 2018).…”
Section: Learning Methods and Theoriesmentioning
confidence: 99%
“…Learning is a cognitive process, where learners process new knowledge based on prior knowledge (Ghadirian et al, 2018); New knowledge is best captured by learners when it is rooted in a context or environment familiar to the learner (Podschuweit and Bernholt, 2018); Experiential learning stimulates knowledge acquisition and processing (Sung et al, 2017;Alstete and Beutell, 2019;Bassi, 2019); New knowledge is first processed by the sensory memory, then by short-term memory, and finally is stored in long-term memory (Nissen and Stenliden, 2020); and Learning is a social activity; learning in small groups is associated with the better achievement of interpersonal skills and positive attitudes toward the learning environment and thinking skills (Wyness and Dalton, 2018).…”
Section: Learning Methods and Theoriesmentioning
confidence: 99%
“…Having a solid grasp of financial knowledge leads to sound decision-making (Zutter and Smart, 2022). The synergistic combination of SBL with traditional lecture-based instruction in the realm of financial management augments the overall learning outcomes (Alstete and Beutell, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These engaging activities improve understanding through virtual experience, skill development and practical decision-making. Simulations are particularly effective in business education and can expose learners to realistic management scenarios and allow them to practice and apply their knowledge and abilities in a safe and controlled environment (Alstete and Beutell, 2019; Alstete and Beutell, 2021). Research has shown that average student engagement levels in business education is higher in simulation and gaming than with traditional course experiences and can produce significantly higher improvements in self-efficacy (Rogmans et al , 2019; Tompson and Dass, 2000).…”
Section: Introductionmentioning
confidence: 99%